2021
DOI: 10.21203/rs.3.rs-1076790/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Social Media Use and the Acceptance of Covid-19 Vaccination Among the General Population in Saudi Arabia – A Cross-sectional Study

Abstract: BackgroundThe 2019 Coronavirus Disease Pandemic (COVID-19) is a worldwide global epidemic. Although acceptance of COVID-19 vaccination will be a critical step in combating the pandemic, achieving high uptake will be difficult, and potentially made more difficult by social media misinformation. This study aimed to examine the association between social media use and acceptance of receiving COVID-19 vaccine among the general population in Saudi Arabia.MethodologyA cross-sectional study was conducted from June 17… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…In contrast, the odds for vaccine resistance were significantly reduced among those who reported that the newspaper was their main source of information during the pandemic. Although the finding of a strong independent association between social media use and vaccine resistance was contrary to previous studies on smaller samples in Saudi Arabia [51,52], this is important considering the wide utilisation of Facebook as the main source of information by many participants during the pandemic. A Facebook IQ survey revealed that more than 95 million people in SSAs access Facebook, with 97% of these doing so on handheld and mobile devices each month.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the odds for vaccine resistance were significantly reduced among those who reported that the newspaper was their main source of information during the pandemic. Although the finding of a strong independent association between social media use and vaccine resistance was contrary to previous studies on smaller samples in Saudi Arabia [51,52], this is important considering the wide utilisation of Facebook as the main source of information by many participants during the pandemic. A Facebook IQ survey revealed that more than 95 million people in SSAs access Facebook, with 97% of these doing so on handheld and mobile devices each month.…”
Section: Discussioncontrasting
confidence: 99%
“…The results align with previous studies linking gender to a greater probability of experiencing post-vaccination side effects and more severe symptoms but differed from prior research indicating that gender has no impact on the side effects. 18,[20][21][22][23] Although there is yet no consensus on the influence of gender on the onset and specific symptoms experienced after COVID-19 vaccination, the results of this study support the need to explain to the female population on the higher possibility of experiencing symptoms that may require or not require hospitalization. All age groups report common symptoms, but the participants who reported no symptoms and who reported mild, moderate, and severe symptoms were comparatively younger (Table 3).…”
supporting
confidence: 53%
“…The commonly reported symptoms coincide with previous reports. 8,[14][15][16][17][18][19][20][21][22][23] However, the results of the study indicated that pre-vaccination infection may influence the onset of certain side effects, such as anosmia and ageusia reported more by those who got infected before vaccination and temporary post-injection inflammation and allergy and rash reported more by those who did not get infected before vaccination. Apart from informing vaccine recipients on the common side effects, it is also important to notify those who did not get infected and those who got infected before vaccination on specific side effects that they might experience.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, according to a study [17], 130 participants denied using social media to spread the word about COVID-19. Having a chronic condition (odds ratio [OR]=0.367, P=0.019), thinking that infertility is a side effect of the COVID-19 vaccine (OR=0.298, P=0.009), worrying about a serious side effect from the vaccine (somewhat concerned: OR=0.294, P=0.022, very concerned: OR=0.017, P0.0001), and deciding to get vaccinated based on information shared on social media (OR=0.260 Multivariate analysis eliminated the influence of social media (OR=0.356, P=0.071) and the perception that vaccination causes infertility (OR=0.0333, P=0.054) on the final decision.…”
Section: People's Willingness To Be Vaccinatedmentioning
confidence: 99%